2023
DOI: 10.3389/fphar.2022.1037131
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia combined with neuroprotective adjuvants shortens the duration of hospitalization in infants with hypoxic ischemic encephalopathy: Meta-analysis

Abstract: Objective: Therapeutic hypothermia (TH) is the current standard of care for neonatal hypoxic-ischemic encephalopathy (HIE), yet morbidity and mortality remain significant. Adjuvant neuroprotective agents have been suggested to augment hypothermic-mediated neuroprotection. This analysis aims to identify the classes of drugs that have been used in combination with hypothermia in the treatment of neonatal HIE and determine whether combination therapy is more efficacious than TH alone.Methods: A systematic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
0
2
0
1
Order By: Relevance
“…A recent systematic review and meta‐analysis demonstrated the breadth of neuroprotective adjuvants to therapeutic hypothermia evaluated in RCTs to date, including γ‐aminobutyric acid receptor agonists (phenobarbital, topiramate), n ‐methyl‐ d ‐aspartic acid receptor antagonists (magnesium sulphate, xenon), neurogenic and angiogenic agents (darbepoetin alpha, erythropoietin), umbilical cord blood cells, glucocorticoids (hydrocortisone), and antioxidants (melatonin) 67 . As recognized by others, 68, 69 magnesium sulphate is not the sole, or indeed favoured agent, in the current quest for an adjuvant to augment therapeutic hypothermia‐mediated neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis demonstrated the breadth of neuroprotective adjuvants to therapeutic hypothermia evaluated in RCTs to date, including γ‐aminobutyric acid receptor agonists (phenobarbital, topiramate), n ‐methyl‐ d ‐aspartic acid receptor antagonists (magnesium sulphate, xenon), neurogenic and angiogenic agents (darbepoetin alpha, erythropoietin), umbilical cord blood cells, glucocorticoids (hydrocortisone), and antioxidants (melatonin) 67 . As recognized by others, 68, 69 magnesium sulphate is not the sole, or indeed favoured agent, in the current quest for an adjuvant to augment therapeutic hypothermia‐mediated neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…La encefalopatía hipóxica isquémica tiene gran relevancia en la discapacidad a nivel mundial, el uso de la tecnología ha favorecido el uso de métodos diagnósticos como la resonancia magnética que confirma que los neonatos no presentan una atrofia cerebral concreta lo que se presume que estas lesiones son causadas en la labor de parto (Ovali, 2022) en el avance clínico demuestran la relevancia del uso de la hipotermia terapéutica como un factor que disminuye la discapacidad grave (parálisis cerebral)(Chin Journal Scientific MQRInvestigar 1379 tasa de discapacidad grave varía entre 42-100 % por lo que el uso de este plan terapéutico podría ayudar a reducir los picos de prevalencia de la discapacidad (Garfinkle et al, 2013). Se ha determinado que la secretoneurina un polipéptido es la encargada del proceso de la angiogénesis así como otros procesos como una citoquina quimiotáctica, angiogénica y en el sistema nervioso; por ejemplo en el caso del sistema nervioso la secretoneurina ayuda a la liberación de la dopamina, en la isquémica existen concentraciones altas en el tejido cerebral y en el suero produciendo un colapso de sangre en el cerebro teniendo un aumento de secreción sérica de secretoneurina en muchos de los casos estos niveles altos han sido encontrados en pacientes que han sufrido una reanimación cardiopulmonar siendo un biomarcador para pronosticar un daño neurológico, en el caso de los recién nacidos este neuropéptido puede ser de gran utilidad utilizado como un biomarcador en la identificación de una encefalopatía hipóxico isquémico después de una asfixia perinatal ya que estos niveles se encuentran en concentraciones más altas en comparación con los recién nacidos a término y sanos, sin embargo se considera necesario realizar estudios más avanzados permitan demostrar si este puede ser un biomarcador completo para un diagnóstico eficaz de la EHI (21)(22)(23)(24).…”
Section: Fisiopatologíaunclassified
“…Although hypothermic therapy is effective for neonatal HIE, the window of opportunity for treatment is narrow ( Walas et al, 2020 ). Hypothermic therapy at 33–34°C for 72 h within 6 h of birth has been shown to be effective in reducing the risk of death or neurological disability ( Mietzsch et al, 2020 ; Ovcjak et al, 2022 ). Therefore, clinicians must make a definitive diagnosis and take therapeutic measures within 6 h of birth.…”
Section: Introductionmentioning
confidence: 99%